THE RELEVANCE OF CIVIL ENGINEERING GRADUATE’S COMPETENCES TO WORK IN CONSTRUCTION INDUSTRY - Metha Wijayanti; Amat Jaedun (Universitas Negeri Yogyakarta, 2019)
This study was aimed at analyzing the competencies that are provided and the relevance of graduate competence of vocational schools to work in the construction industry. The evaluation study used was a discrepancy model by identifying gaps between the needs of construction industry competencies and the competencies of Building Engineering graduates. The objects of the study were company owners, heads of the Human Resources Department, and head of the Building Engineering Expertise Program. The data were retrieved using a questionnaire with 60 open statements. The instruments were prepared based on the Director General of Secondary Education Decree Number 7013/D/KP/2013 which is adjusted to the theory of competence and competency of the pre-survey results. The data then were analyzed using quantitative descriptive analysis technique. The results of the study showed that industry requires seven attitude competencies, seven knowledge competencies, and six skills competencies. Industrial competency requirements that are relevant to the competencies supplied by Vocational Schools are six attitude competencies, five knowledge competencies, and one skill competency with a level of relevance in the high category which shows that vocational school graduates are competent to work in the construction industry.RELEVANSI KOMPETENSI LULUSAN SMK TEKNIK BANGUNAN UNTUK BEKERJA DI INDUSTRI KONSTRUKSIPenelitian ini bertujuan untuk menganalisis kompetensi yang dibekalkan dan tingkat relevansi kompetensi lulusan Sekolah Memengah Kejuruan (SMK) Teknik Bangunan untuk bekerja di industri jasa konstruksi. Penelitian evaluasi menggunakan model diskrepansi dengan mengidentifikasikan kesenjangan antara kebutuhan kompetensi industri konstruksi dan kompetensi lulusan Teknik Bangunan. Objek penelitian adalah pemilik perusahaan, kepala Human Resources Departement (HRD), dan kepala Program Keahlian Teknik Bangunan. Pengambilan data menggunakan kuesioner dengan 60 pernyataan terbuka. Instrumen disusun berdasarkan Keputusan Direktur Jenderal Pendidikan Menengah Nomor 7013/D/KP/2013 yang disesuaikan dengan teori kompetensi dan kompetensi hasil prasurvei. Data dianalisis dengan menggunakan teknik analisis deskriptif kuantitatif. Hasil penelitian menunjukkan kompetensi yang sangat dibutuhkan industri adalah tujuh kompetensi sikap, tujuh kompetensi pengetahuan, dan enam kompetensi keterampilan. Kebutuhan kompetensi industri yang relevan dengan kompetensi yang dibekalkan SMK adalah enam kompetensi sikap, lima kompetensi pengetahuan, dan satu kompetensi keterampilan dengan tingkat relevansi dalam kategori tinggi yang menunjukkan bahwa lulusan SMK kompeten untuk bekerja di industri konstruksi.